Exploring the pharmaceutical outsourcing industry’s challenges and its resilience in the face of the COVID-19 pandemic - Chowdhary, Vikram Singh (2024)
The outsourcing projects in the pharmaceutical industry involve extensive research and meticulous coordination among various partners; if not executed correctly, they could result in severe financial and regulatory implications. Given the disruptive global scenario, the challenges and stakes for such activities involving multiple stakeholders appear exceptionally high. As the world grapples with the aftermath of the COVID-19 pandemic, conducting a comprehensive examination of how the intricately interconnected pharmaceutical outsourcing industry managed its operations during these unprecedented times becomes imperative. The objective of this research is to illuminate the challenges encountered by outsourcing activities in the pharmaceutical industry due to the pandemic and assess the resilience demonstrated by industry professionals. Employing the phenomenological approach, this study conducted in-depth interviews with twenty-five senior industry professionals from diverse geographic regions. The findings reveal the challenges faced by both global and local pharmaceutical companies during the COVID-19 pandemic engaged in outsourcing activities, underscoring the vulnerability of global health systems to external shocks. The research underscores substantial operational challenges across domains, encompassing manpower, IT infrastructure, communications, and supply chains. The study provides valuable insights for industry managers to navigate future uncertainties and emphasizes the pivotal role of digital technologies and robust supply chains in ensuring organizational resilience.